Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. Agile Internal Audit from the Perspectives of Saudi Internal Auditors: An Exploratory StudyMr. Anan Abdulaziz Almahyawi, Co-Prof. Fahdah Sultan Alsudairi2. Violations of concealment of economic activities in the Saudi LegalDr. Waleed Ali Daghriri3. The reality of administrative training in Aseer Education Administration and the obstacles to its development from the employees' point of viewMrs. Mona Ahmed Yahya Al-Marhi, Mrs. Sohair Ahmed Mohammed Al-Ghamdi, Mrs. Nouf Saleh Saeed Bahashwan, Prof. Bader Saleh Al-Abdi4. The impact of leadership styles on the performance of workers in health organizations, An applied study in Asir Central Hospital during 2021Mr. Nabil Ali Saeed Alshahrani5. The relationship between being in places intended for the use of narcotic drugs and psychotropic substances – A descriptive and analytical study –Dr. Hakami, Hafiz Mohammed6. A reading of the Qatari state's trends from the Syrian crisis 2011 – 2018Dr. OUASSFI BEN MUSSA7. Using (TOPSIS) technique for decision-making in Managerial Accounting: A case studyDr. Ahmad Husain Alyaseer8. Evaluating Corporate Social Responsibility Reporting Practices in the Sultanate of Oman (2016 to 2018)Mr. Sultan Said Al-Maauli
Keywords: The Journal of Economic, Administrative and Legal Sciences